Associations between modifiable lifestyle behaviors and mental health indicators in adolescents from 48 countries: a cross-sectional study - De Moraes-Ferrari, G (BioMed Central Ltd, 2026)
Background: Lifestyle factors are known to be associated with mental health indicators. However, further studies are needed to explore how these associations manifest across different sociodemographic contexts. This study aimed to evaluate the association between modifiable lifestyle behaviors and mental health indicators among adolescents from 48 countries participating in the Global School-Based Student Health Survey (GSHS), considering each country’s Human Development Index (HDI) to account for sociodemographic differences. Methods: This cross-sectional study used data from national surveys conducted through the GSHS, including school-aged adolescents (10–19 years). Modifiable behaviors (obesity, fruit and vegetable consumption, physical activity, sitting time, transportation to school, tobacco and alcohol consumption and school attendance) and mental health indicators (anxiety, loneliness, suicidal thoughts and suicide planning) were obtained by self-reported questionnaire and categorized. Results: The final sample comprised 146,177 adolescents (54.2% female). Obesity, low fruit and vegetable consumption, physical inactivity, tobacco and alcohol use, and low school attendance were significantly associated with poor mental health indicators. Tobacco and alcohol use were strongly associated with anxiety (OR: 1.91; 95% CI: 1.81–2.02 and OR: 1.65; 95% CI: 1.58–1.73, respectively), loneliness (OR: 1.65; 95% CI: 1.57–1.74 and OR: 1.40; 95% CI: 1.34–1.46), suicidal ideation (OR: 2.57; 95% CI: 2.46–2.69 and OR: 2.06; 95% CI: 1.99–2.14), and suicide planning (OR: 2.49; 95% CI: 2.38–2.61 and OR: 1.98; 95% CI: 1.91–2.06), regardless of sex, age, and region. The strength of these associations varied according to country HDI. Conclusion: The associations between lifestyle behaviors and mental health indicators varied across HDI categories. However, tobacco use, alcohol consumption, and inadequate school attendance were consistently associated with anxiety, loneliness, suicidal ideation, and suicide planning at all HDI levels. These modifiable factors represent key targets for prevention strategies, underscoring the need for interventions that consider socioeconomic disparities. © The Author(s) 2025.